Nonfragile control design for consensus of semi‐Markov jumping multiagent systems with disturbances - Sakthivel, Rathinasamy; Parivallal, Arumugam; Huy Tuan, Nguyen; Manickavalli, Subramanian (International journal of adaptive control and signal processing, 2021)
Summary The consensus problem for multiagent systems (MASs) with semi‐Markov jumping parameters under the influence of disturbances is investigated in this article. In the first part of this article, an extended dissipative approach is used for the consensus of MASs with semi‐Markovian jumping parameters and external disturbances via nonfragile controller with randomly occurring gain fluctuations. Besides, in the second part of the article, the consensus of stochastic semi‐Markovian jumping MASs via nonfragile controller subject to probabilistic time‐varying delay is discussed. The primary motive of this article is to develop a robust controller such that the considered MASs with semi‐Markov jumping parameters achieve consensus in the presence of external disturbances. For this, the chosen problems are first converted to stabilization problems then by using Lyapunov stability theory and linear matrix inequality approach, the stabilization criterion have been established. At last, two numerical examples are worked out to illustrate the efficiency of the proposed control methodologies.